Social Movements and Energy Democracy: Types and Processes of Mobilization - Hess, David J. (Frontiers in Energy Research, 2018)
An important but sometimes overlooked dimension of the study of energy, democracy, and governance is the role of social movements. Industrial transition movements (ITMs) emerge when there is resistance from incumbent organizations, such as large utility companies in the electricity industry, to grassroots efforts to change the industry. A classification of ITM goals is developed based on two types of sociotechnical transition goals (developing alternative technologies and ending existing technologies) and two types of societal change goals (the democratization of industrial organizations and political processes and the equitable access to jobs and industrial products). The study of processes and outcomes of ITMs also has implications for social movement theory, which are outlined. This approach enables a comprehensive analysis of the relations among the state, industry, civil society, and social movements that can identify causal mechanisms in the effects of social movements on industrial transitions and energy democracy.